Implikasi Putusan Mahkamah Konstitusi No 91/PUU-XXVIII/2020 Terhadap Pemenuhan Hak Pekerja Waktu Tertentu - Soplantila, Ronny (Jurnal Saniri, 2022)
After the enactment of Law No. 11 of 2020 Concerning Job Creation, there are several changes regarding the provisions of work agreements for a certain time, including changes to the period, extension and renewal of work agreements and compensation money, the workers disagree and reject this so they submit a Judicial Review to the Constitutional Court. Finally it was granted by the Constitutional Court with the issuance of decision Number 91/PUU-XVIII/2020 which stated that the formation of a work copyright law does not have conditionally binding legal force as long as it does not make changes within 2 years or in other words this decision is conditionally unconstitutional. Of course this will have an impact on workers related to legal certainty and in particular for the guarantee of the fulfillment of rights for workers. This type of research is normative legal research using the approach of statutory regulations, legal principles and expert opinion. Special attention is needed from the government, in this case legislators, to immediately make changes to the Job Creation Law, where it is hoped that these changes can accommodate the aspirations of workers